Result of Ongoing Reforms in Social Support of the Population of New Uzbekistan - Khojalepesov Polat Zinatdinovich; Madetova Nilufar Maxkamjan qizi; Jenghisbaeva Dilnaz Bakhadirovna (Peerian Journals Publishing, 2023)
The article presents the problems of overcoming poverty in a market economy, as well as the effectiveness of the ongoing social policy. The tasks of effectively overcoming poverty using new methods are also considered. The article also talks about the development of entrepreneurship and family business in mahallas.
Keywords: social policy; economic development; entrepreneurship; unemployment